Pengaruh Kepemimpinan dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT. Sinar Sosro Tanjung Morawa Medan - Ahmad Aji Rahman; Yusniar Lubis; Khairul Saleh (Universitas Medan Area, 2019)
This study aims to determine the effect of leadership and work environment affect the performance of employees. The proposed hypothesis is the influence of leadership on the performance of the employee, the work environment influence on employee performance and simultaneously also in his second test as well. Samples were production employees at PT.Sinar Sosro Tajung Morawa Medan totaling 30 respondents. The sampling technique was random method. Methods of data collection using random methods, questionnaires, and interviews. Data analysis using Multiple Linear Regression and also using some test that is test validitas, realibity test, t test and f. Based on test results obtained Data Regression that that leadership and work environment greatly affect the performance of the employee, his great influence up to 86% to show that leadership and work environment in Tanjung Morawa at PT.Sinar Sosro very positive effect.